Effects of amino acid value-added urea on rice growth and nitrogen utilization. - Lin Cheng; Zongya Wang; Shuangshuang Huang; Hongyan Wu; Ruichao Li (PLoS ONE)
To investigate the impact of amino acid value-added urea on rice growth and nitrogen utilization, this study aimed to provide insights into enhancing the quality and efficiency of traditional nitrogen fertilizers using small molecule active substances. Amino acids were added at 5‰ and 5% levels to create different levels of amino acid value-added urea (AU0.5 and AU5) by blending with urea as test materials. Pot experiments were conducted using 'Liangyouhua 6' rice as the test crop, with four treatment groups: non-urea (CK), regular urea (U), and amino acid value-added urea (AU0.5, AU5) at two different addition ratios. All treatments, except the control, had the same application rates of nitrogen, phosphorus, and potassium. After harvesting the rice, plant and soil samples were collected from various depths to analyze the nutrient composition of rice, nitrogen content of fertilizer in different soil layers, and 15N abundance. The results showed that amino acid-added urea significantly enhanced biomass accumulation in different parts of rice. Compared to U, rice straw and grain biomass increased by 25.27% to 32.74% and 21.71% to 27.77% under AU0.5 and AU5 treatments, respectively. In terms of nitrogen application, effective panicle and grain numbers per panicle in AU0.5 and AU5 rice were 17.37% to 21.05% and 8.76% to 15.33% higher than in U, with a significant difference between AU0.5 and U. Furthermore, total aboveground nitrogen and fertilizer nitrogen accumulation in rice treated with AU0.5 and AU5 increased by 3.59% to 5.09% and 3.31% to 8.49%, respectively, compared to U. The accumulation of fertilizer nitrogen in grains and leaves also showed increases of 2.86% to 6.32% and 4.38% to 16.25%, respectively, compared to U. This study found that the application of amino acid value-added urea had a significant impact on the accumulation of fertilizer nitrogen in straw. Further analysis showed that it improved both the apparent nitrogen utilization efficiency and fertilizer nitrogen utilization efficiency. Compared to ordinary urea, the apparent nitrogen utilization efficiency of AU0.5 and AU5 increased by 23.71% and 33.93%, respectively, while the utilization efficiency of 15N increased by 15.66% and 6.78%, respectively. The residual fertilizer nitrogen in soil treated with amino acid value-added urea was mainly found in the 0-30cm soil layer, reducing nitrogen leaching downwards. Additionally, the nitrogen loss rate was significantly lower (reduced by 12.39%-12.97%) compared to regular urea. The difference between AU0.5 and AU5 was not significant, but AU5 showed an 18.80% higher fertilizer nitrogen residual rate than U. Overall, the study concluded that amino acid value-added urea promoted rice growth by enhancing nitrogen absorption, improving transport to grains, increasing nitrogen fertilizer efficiency, reducing nitrogen leaching, and lowering nitrogen loss rate. The best results were observed with the addition of 5‰ amino acid.